A SAM-based Model, constructed from the SNA, to be used for studying the distributional impacts of government policies in Portugal - Santos, Susana (2009)
An attempt will be made to study the impacts of government policies on the distribution of income, paying close attention to the corresponding response of the different macroeconomic aggregates and balances. The Social Accounting Matrix (SAM) will be chosen as the working instrument. A numerical version of the SAM, constructed from the System of National Accounts (SNA), will serve as the basis for the construction of an algebraic version of the same matrix for Portugal. This methodological choice was linked to the fact that, underlying the SAM, there are interrelated subsystems that, in the numerical version of the matrix, provide an analytical picture of the circular flow or general equilibrium interactions of the market economy, when studied during a particular accounting period. On the other hand, in the algebraic version of the SAM, it is possible to measure and quantify the economy-wide effects of changes in the particular nominal flows represented by the numerical version (injections from and leakages into the system), which might be the result of policy measures. To this end, a computable (numerically solvable) general (economy-wide) equilibrium (macroeconomic balance) approach will be adopted. A SAM-based model will be constructed in perfect consonance with the SNA, in which each cell is defined with a linear equation or system of equations, whose components are all the known and quantified transactions of that system, using the parameters of the numerical SAM that served as the basis for this model. Scenarios will be defined and analysed from experiments carried out in relation to the distributional impact of government policies.